Evolution of Land and Life in Oman: an 800 Million Year Story - Al Kindi, Mohammed Hilal (Springer International Publishing, 2018)
This book takes readers on a fascinating journey to discover the story of land and ancient life evolution in Oman since at least 800 million years ago. Oman is well known for its marvelous geology. What tectonics affected this part of the world and what organisms lived there? How did the climate and life develop? Did life forms become more complex and varied or become extinct and disappear forever? The book thoroughly reconstructs this land and ancient life evolution and offers readers an understanding on how land, climate and life have proceeded and developed in Oman through the millions of years.